The role of cultural heritage sites in the creation of tourism potential of small towns in Poland - Kwiatek-Sołtys, Agnieszka; Bajgier-Kowalska, Małgorzata (European Spatial Research and Policy, 2019)
Historical sites may be found in nearly all small towns in Poland. Some are listed by UNESCO as World Heritage Sites. The purpose of the paper is to discuss the role of these resources in the broader set of elements shaping the tourism potential of towns, and also to illustrate the regional differences among small towns in Poland in terms of their potential to develop a local or regional tourism sector. The study provides a typology of towns based on local natural and landscape elements, cultural heritage resources as well as hotels and other tourist accommodations. The statistical data discussed in this paper was obtained from the Local Data Bank of Statistics Poland for the period 2012–2014, while historical sites were chosen from the National Heritage Board of Poland. The study covers all small towns in Poland and has shown unequivocally that the presence of a historical site is not necessarily a factor in the overall development of a local tourism sector. The cultural resources appear to be an undervalued asset, which can be used to develop a local tourism sector, especially in towns which are searching for new development paths.